2014
DOI: 10.1155/2014/726313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Different Fertilizer Sources on the Growth and Nutrient Content of Moringa (Moringa oleifera) Seedling in a Greenhouse Trial

Abstract: A greenhouse experiment was conducted to investigate the effects of NPK, poultry manure, and organomineral fertilizer on the growth and nutrient concentration ofMoringa oleiferaleaves. The experimental design was completely randomized design (CRD) with four treatments replicated three times. Data collected were analysed using descriptive statistics and ANOVA atP=0.05. Growth parameters measured include number of leaves per plant, plant height (cm), and stem girth (mm). The application of poultry manure increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 5 publications
4
32
2
6
Order By: Relevance
“…Compost types and mineral fertilizer were more effective, as they provided more mineral elements such as N, P, K, Ca, N, Mg and C for plant growth and development. Dania et al (2014) obtained similar results, the nitrogen of M. oleifera leaves being significantly improved by Poultry manure with 4.13% compared to the organomineral fertilizer (2.01%).…”
Section: Variation In the Mineral Composition Of M Oleifera At 55 Dasupporting
confidence: 60%
“…Compost types and mineral fertilizer were more effective, as they provided more mineral elements such as N, P, K, Ca, N, Mg and C for plant growth and development. Dania et al (2014) obtained similar results, the nitrogen of M. oleifera leaves being significantly improved by Poultry manure with 4.13% compared to the organomineral fertilizer (2.01%).…”
Section: Variation In the Mineral Composition Of M Oleifera At 55 Dasupporting
confidence: 60%
“…Abdullahi et al [24] recommended that the combination of 20,000 stands per hectare and a fertilizer application rate of 200 kg N per hectare is the optimum one for the cultivation of Moringa oleifera for biomass production in the North-Central zone of Nigeria, where the area is characterised by hot summer temperatures and high rainfall of up to 1300 mm/a. Dania et al [25] further reported that the application of poultry manure significantly increased the vegetative growth of this crop.…”
Section: Effect Of Plant Density On Biomassmentioning
confidence: 93%
“…Sánchez et al [12] applied fertilizer at a rate of 90 kg N/ha as urea, 30 kg P/ha (P 2 O 5 ), and 30 kg K/ha (K 2 O). Further findings by Dania et al [25] revealed that the nutrient concentration of moringa leaves was significantly improved by treating degraded soil with poultry manure. Under high rainfall and temperature conditions, application of nutrients to the soil will improve plant growth and the chemical composition of the plants.…”
Section: Effect Of Planting Density and Cutting Frequency On Chemicalmentioning
confidence: 98%
“…Several studies [7,10,11], focused on leaves or biomass production, suggest that the vegetative growth of Moringa is best supported by 120 kg N:P:K/ha. Fertilization must be done during soil preparation before sowing, and when the trees are at the onset of the growth period, i.e., just before the rainy season.…”
Section: Cultivation For Seed Productionmentioning
confidence: 99%